The Troubadours - Koons, Lawrence F. (Indiana University Press, 1967)
Combining extraordinary learning with grace of style, Robert Briffault provides in this volume the first comprehensive work in English on the heritage of the medieval troubadours, the traveling "reporters" and often the sole entertainers of their age. The lays which these remarkable poets sang, with their intense lyricism and unique treatment of erotic themes-so unlike that found in the literature of Greece or Rome or of barbarian cultures-sprang from the Provencial lands of southern France. Here, in the twelfth century, the popularity of Islamic songs of the neighboring Hispano-Mauresque civilization contributed to the development of a poetry which "answered the mood of a feudal society newly awakened to its native uncouthness by contact with the luxury of the Orient." Briffault clearly establishes that the largely non-Western idiom of the troubadours soon dominated the language of European poetry. His provocative essays on Dante and Shakespeare illuminate the particular impact of the troubadour tradition, so long ignored by literary historians, on Italian and English verse.